"To Struggle Up a Never-Ending Stair": Theodicy and the Failure It Gifts to Black Liberation Theology. Issue 3 (1st September 2020) - Calloway, Jamall A.
ABSTRACT: There has been much criticism – and an overall unfortunate dismissal – of William R. Jones' Is God A White Racist?: A Preamble to Black Theology (1973) in the literature of Black liberation theology. What is undertheorized, however, is the constructive possibilities of Jones' work. Analyzing the theological debate between Jones and James H. Cone provides us with the necessary material in order to construct a Black theology that commences with the assumptions of Jones' theodicy. I argue that theodicy is a useful "controlling category" for Black liberation theology, but only – and here I am following Kant – as a result of how its collapses rational arguments for believing in God/liberation. And it is precisely this failure that makes it profoundly useful as an avenue into understanding the contours of "Black faith" that undergirds Black liberation theology.